A "Closed‐Loop" Therapeutic Strategy Based on Mutually Reinforced Ferroptosis and Immunotherapy. (1st February 2022) - Du, Yaqian; Zhang, Rui; Yang, Jiani; Liu, Shikai; Zhou, Jialing; Zhao, Ruoxi; He, Fei; Zhang, Yanqiao; Yang, Piaoping; Lin, Jun
Abstract: The immunosuppression and immune escape of current immunotherapy result in low efficacy, and ferroptosis is greatly restricted by the low reactive oxygen species (ROS) production efficiency. Here, for the first time a "closed‐loop" therapy based on photothermal enhancement of ferroptosis and immunotherapy stimulated by each other on a multifunctional nanoplatform is reported. This platform is composed of copper silicate and iron silicate mesoporous hollow nanospheres, followed by in situ growth of Au nanoparticles and loading of an immune adjuvant resiquimod R848. The laser irradiation‐mediated heat and the introduction of copper ions significantly enhance ROS generation, leading to the simultaneous depletion of glutathione peroxidase 4 (GPX4) and glutathione (GSH). The onset of ferroptosis in tumor cells is thus enhanced and an immune response with immunogenic cell death (ICD) is triggered, promoting the dendritic cells (DCs) maturation and T cell infiltration. Interferon γ (IFN‐γ) released from CD8 + T cells downregulates the expression of SLC7A11 and GPX4, which in turn enhances ferroptosis expression, thus constituting a "closed‐Loop" therapy. Importantly, this system is effective in both killing the primary tumor and inhibiting tumor metastasis. The proposed "closed‐loop" therapeutic strategy may provide a guidance for the design of future antitumor nanoplatforms. Abstract : A "closed‐loop" therapy is proposed based on mutually reinforced ferroptosis and immunotherapy on a multifunctional nanoplatform (CISAR). The enhanced reactive oxygen species generation and consumed GPX4 induce obvious ferroptosis. The body has a strong immune response with immunogenic cell death, resulting in T cells infiltration. IFN‐γ downregulates SLC7A11 and GPX4 expression, which in turn reinforce ferroptosis expression.